IDENTIFYING STUDENTS' PERCEPTION IN LEARNING ENGLISH VOCABULARY THROUGH FAST VOCABULARY GAME - Amanda, Esti; Nadrun, Nadrun; Wahyudin, Wahyudin; Rofiqoh, Rofiqoh (e-Journal of ELTS (English Language Teaching Society), 2023)
This research aims to discover students' perception of learning English vocabulary through Fast Vocabulary Game. A qualitative approach was used in this research. The subject was the grade VII students at SMPN 2 Dapurang Pasangkayu who have experienced using the Fast Vocabulary Game. The instruments used were questionnaires and interview questions. There were nine questions in the questionnaires filled out by five respondents. Two informants answered five questions in the interview. The result indicates that students' perception of learning English vocabulary through Fast Vocabulary is dominantly positive. Learning English vocabulary using the game is easy, enjoyable, fun, and accessible as long as an internet connection is available. The vocabulary that is available in the game is easy to understand. Fast vocabulary game makes it easier for students to learn and memorize new vocabulary.